Isolation of a Novel Flavanonol and an Alkylresorcinol with Highly Potent Anti-Trypanosomal Activity from Libyan propolis - Weam Siheri; Godwin U. Ebiloma; John O. Igoli; Alexander I. Gray; Marco Biddau; Pilaslak Akrachalanont; Samya Alenezi; Mohammad A. Alwashih; RuAngelie Edrada-Ebel; Sylke Muller; Catherine E. Lawrence; James Fearnley; et al. (Molecules, 2019)
Twelve propolis samples from different parts of Libya were investigated for their phytochemical constituents. Ethanol extracts of the samples and some purified compounds were tested against Trypanosoma brucei, Plasmodium falciparum and against two helminth species, Trichinella spiralis and Caenorhabditis elegans, showing various degrees of activity. Fourteen compounds were isolated from the propolis samples, including a novel compound Taxifolin-3-acetyl-4’-methyl ether (4), a flavanonol derivative. The crude extracts showed moderate activity against T. spiralis and C. elegans, while the purified compounds had low activity against P. falciparum. Anti-trypanosomal activity (EC50 = 0.7 µg/mL) was exhibited by a fraction containing a cardol identified as bilobol (10) and this fraction had no effect on Human Foreskin Fibroblasts (HFF), even at 2.0 mg/mL, thus demonstrating excellent selectivity. A metabolomics study was used to explore the mechanism of action of the fraction and it revealed significant disturbances in trypanosomal phospholipid metabolism, especially the formation of choline phospholipids. We conclude that a potent and highly selective new trypanocide may be present in the fraction.